2008
DOI: 10.1111/j.1440-1681.2008.04913.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Sympathetic, Respiratory and Somatomotor Outflow by an Intraspinal Pattern Generator

Abstract: 1. Sympathetic and somatic motor outflow results from the summation of excitatory and inhibitory inputs arising from intra- and supra-spinal origins. Here we determined the contribution of intra- and supra-spinal GABAergic inputs, utilizing GABA-A receptors, in producing sympathetic and somatic motor outflow. 2. Spinal GABA-A receptor blockade, with bicuculline or picrotoxin injected intrathecally at T9, increased the level and lability of arterial pressure, sympathetic (splanchnic and cervical sympathetic) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Moreover, in our previous study, we reported that transection at the C1 level leaves the effects of i.t. bicuculline infusion unaltered (Goodchild et al ., 2000; 2008) and i.t. administration of drugs appear not to spread more than a few segments away from the site of administration (Yaksh and Rudy, 1976) and are able to penetrate around 2 mm (Yamada et al ., 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in our previous study, we reported that transection at the C1 level leaves the effects of i.t. bicuculline infusion unaltered (Goodchild et al ., 2000; 2008) and i.t. administration of drugs appear not to spread more than a few segments away from the site of administration (Yaksh and Rudy, 1976) and are able to penetrate around 2 mm (Yamada et al ., 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The spinal cord was anaesthetized at the C8 level by microinjection of a local anaesthetic, bupivacaine (500 nL, AstraZeneca, Australia) into the middle of each hemi‐spinal cord in four animals. These injections were always adequate to cause blood pressure and sympathetic nerve activity to fall to levels equivalent to that seen following spinal transection at the C8 level (Goodchild et al ., 2008). Following local anaesthetic injection at C8, OX‐A (20 nmol) or PBS was injected i.t.…”
Section: Methodsmentioning
confidence: 99%
“…37 The existence of a spinal CPG for respiration has been primarily investigated and shown in isolated (in vitro) brainstem-spinal cord preparations and slices from neonatal rats. [17][18][19][20] However, in anesthetized adult rats, spontaneous recovery of the spinal CPG for respiration after high cervical transection has not been oberved [24][25][26] . It is possible that anesthesia may suppress the spinal network responsible for recovery of inspiratory phasic discharges after high cervical transection.…”
Section: Figure Legendsmentioning
confidence: 98%
“…21 In the anesthetized state, spontaneous phasic activity in PhN discharge was not observed following transection in numerous publications, but has been shown in dogs. 12,13,[23][24][25][26][27] Previous works have shown that the upper cervical (C 1 -C 2 ) segments contains only inspiratory neurons in cats and monkeys and inspiratory (~90%) and expiratory (~10%) units in rats [28][29][30] . It has been proposed that this group may provide excitation to inspiratory and inhibition to expiratory motoneurons via spinal interneurons [28][29][30] .…”
Section: Figure Legendsmentioning
confidence: 99%
“…Intraspinal coupling of sympathetic and motor systems is supported by the observation of NMDA-induced correlated motor and sympathetic output in a perfused trunk-hindquarters preparation of the adult mouse (Chizh, et al, 1998). Similarly, in vivo measurements in the rat cervicothoracic spinal cord (spinalized at C1) exhibit correlated sympathetic and motor activity in the presence of intrathecal GABA-A antagonists (Goodchild, et al, 2008). Thus, spinal interneurons common to sympathetic and motor systems could account for the simultaneous modulations in vascular conductance and flexor reflexes observed in the current study.…”
Section: Discussionmentioning
confidence: 97%